2022
DOI: 10.3390/life12071030
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal-Stem-Cell-Derived Extracellular Vesicles Attenuate Brain Injury in Escherichia coli Meningitis in Newborn Rats

Abstract: We recently reported that transplantation of mesenchymal stem cells (MSCs) significantly reduced bacterial growth and brain injury in neonatal meningitis induced by Escherichia coli (E. coli) infection in newborn rats. As a next step, to verify whether the MSCs protect against brain injury in a paracrine manner, this study was designed to estimate the efficacy of MSC-derived extracellular vesicles (MSC-EVs) in E. coli meningitis in newborn rats. E. coli meningitis was induced without concomitant bacteremia by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, when the antibiotics were combined with MSC-EVs, the inflammation and subsequent brain damage were significantly reduced. This suggests that therapy based on MSC-EVs may offer a novel approach to the treatment of neonatal meningitis by utilizing the anti-inflammatory and immunomodulatory properties of MSC-EVs [ 190 ].…”
Section: Experimental Studies Of Evs As Therapeutic Tools For Neonata...mentioning
confidence: 99%
“…However, when the antibiotics were combined with MSC-EVs, the inflammation and subsequent brain damage were significantly reduced. This suggests that therapy based on MSC-EVs may offer a novel approach to the treatment of neonatal meningitis by utilizing the anti-inflammatory and immunomodulatory properties of MSC-EVs [ 190 ].…”
Section: Experimental Studies Of Evs As Therapeutic Tools For Neonata...mentioning
confidence: 99%
“…The extracellular vesicles used exclusively as clinical treatments for the modulation of neonatal astrogliosis could be manufactured as off-the-shelf medicine, also facilitating their application outside the neonatal intensive care unit (NICU). To date, the promising effectiveness of stromal/mesenchymal stem cell transplantation in governing neonatal astrogliosis has been demonstrated by many studies dedicated to perinatal asphyxia, intraventricular hemorrhages, and infections [169][170][171][172][173].…”
Section: Crosstalk Between Neural Cells In the Developing Brainmentioning
confidence: 99%
“…MSC-derived EVs (MSC-EVs) are now well established as potential therapeutics due to their regenerative potential and immune modulation [ 3 , 7 , 8 , 9 , 10 , 11 ]. A research article reported a novel therapeutic effect of MSC-EVs on meningitis in newborn rats induced by Escherichia coli ( E. coli ) [ 12 ]. Intra-cerebroventricular transplantation of MSC-EVs attenuated brain cell death, reactive gliosis, and inflammation including the number of active microglia and the production of inflammatory cytokines, while there was no significant effect on bacterial growth.…”
mentioning
confidence: 99%